The Development Of The Use Of Social Media Marketing Rs: How Far Has It Been? - Tjindrawati Ongko (Jurnal Indonesia Sosial Teknologi, 2023)
The use of hospital social media marketing has become a necessity and a common thing, needed, to be a trend in the current marketing era even though not all hospitals are ready to use it effectively and efficiently. All hospitals are developing these relatively new and fast-growing marketing "tools" trying to find suitable marketing patterns and forms. This article seeks to review how far the development of the use of social media marketing in several hospitals simply, namely Adi Husada Undaan Wetan Hospital Surabaya, Siloam Hospital Surabaya, Mount Elizabeth Group Hospital; based on data that can be obtained, reviews and observations and also know more about the reasons for the use and development of social media marketing by one of the hospitals in Surabaya, namely Adi Husada Undaan Wetan Hospital Surabaya